Wikiplantbase #Toscana, breaking the dormancy of floristic data. (3rd May 2016) - Bedini, G.; Pierini, B.; Roma-Marzio, F.; Caparelli, K.F.; Bonari, G.; Dolci, D.; Gestri, G.; D'Antraccoli, M.; Peruzzi, L.
Abstract : The online platform "Wikiplantbase #Toscana" provides a framework where the full set of georeferenced floristic records of Tuscany (central Italy) can be entered, stored, updated and freely accessed through the Internet. As of 5 January 2015, the database stores 67, 360 floristic records, referable to 3578 accepted specific and subspecific taxa. Most records are based on published data (80.6% of the total), then by published herbarium specimens (15.1%) and on unpublished field data (3.8%); unpublished herbarium records account only for 0.5% of the stored data. At present, the most represented species is the fern Pteridium aquilinum (L.) Kuhn subsp. aquilinum (Dennstaedtiaceae) with 234 records for 219 localities, but 625 species are still represented only by one record for a single locality. Data acquisition is far from complete, but in slightly more than one year a massive amount of data was accumulated, and can be maintained up-to-date with relatively little effort. This could power several researches such as, for example, (1) taxonomic researches especially on species and genera in Tuscany and Italy; (2) studies on the distribution of diversity across administrative or ecological boundaries; (3) evaluation of conservation status of endangered taxa; and (4) static and dynamic range modelling and evolution niche studies.